Telepsychiatry and Telepsychotherapy: Critical Issues Faced by Indian Patients and Psychiatrists. Issue 5 (October 2020) - Sousa, Avinash De; Shrivastava, Amresh; Shah, Bhumika
Telepsychiatry and telepsychotherapy are new treatment modalities that have been used more than ever during the COVID-19 pandemic. There are many challenges that are faced with the use of this modality for both patients and psychiatrists alike. There are critical issues faced with regard to the development of rapport, managing the entire teleconsultation set up, privacy and issues related to fees, issues related to prescribing and monitoring, and issues while handling emergencies. The challenges faced are discussed and some solutions if possible are laid out.